Evaluation of potential plant crude extracts against green stink bug Nezara viridula Linn. (Hemiptera: Pentatomidae) - Asmanizar,; Aldywaridha,; Sumantri, Edy; Lubis, Ratna Mauli; Siregar, Diapari; Fenti Maimunah, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2019)
The Green Stink Bug Nezara viridula (Hemiptera: Pentatomidae) is an important pest of soybean crop in Indonesia, causing losses of seed production. A study was conducted to evaluate the insecticidal potential crude extract on the mortality of Green Stink Bug, N. viridula. Fourteen of crude extracts used in this study were extracted by Soxhlet extractor. The experiment was conducted using residual toxicity (contact poison) by applying crude extract solution of 0.5 and 0.25% (volume of extract/volume of water, v/v) on adult N. viridula. Results revealed that N. viridula mortality was affected significantly by crude extracts. The crude extracts of Annona muricata seed, Alpinia galanga rhizome and Jatropha curcas seed, at 0.5 and 0.25% concentration showed insects mortality up to 80-100%. Whilst, crude extracts of Citrus aurantifolia peel, Carica papaya leaf, Lantana camara leaf, Tagetes erecta leaf, Ageratum conaizoydes plant, Cymbopogon nardus leaf and Murraya koenigii leaf caused insect mortality between 45.00 to 72.5%. Probit analysis showed that J. curcas seed crude extract was highly toxic (LC50=0.026%) to N. viridula adult followed by A. galanga rhizome crude extract (LC50=0.031%) and A. muricata seed crude extract (LC50=0.038%). These crude extracts proved to be highly potent to control N. viridula. Further studies are needed to actually verify these crude extracts and its potential application as botanical insecticides.